Quality and acceptability of velvet bean (mucuna pruriens) foliage ensiled with whole plant maize by West Africa dwarf sheep (2014)
This experiment was conducted to determine the suitability of Velvet Bean Foliage (VBF) and Whole Plant Maize (WPM) silage as dry season feed for ruminants in Southwest of Nigeria. In this study, WPM was ensiled with five levels of VBF (0, 25, 50, 75 and 100%). Physical characteristics, temperature, pH and proximate composition of the silages were assessed after 21 days of ensiling. Preference for the silage by ruminants was determined using twelve West African dwarf (WAD) rams. Results revealed that pH, temperature and physical characteristics of all silages were within acceptable range except for VBF -100 which did not make good silage. The appearance, smell and texture of all the silage mixtures compromised increasing level of VBF while the pH increased. The pH of the silage varied from 3.92-7.98. Dry matter (DM), crude protein (CP) and crude fibre (CF) concentration in the silages ranged from 20.67 - 26.65, 8.02 - 15.77, 26.42 - 1926g/100g, respectively. The DM and CF of the silages reduced with increasing level of VBF in the mixture while the CP increased. Coefficient of preference (CoP) for the silage varied from 0.79 to 1.13 while percentage preference varied from 15.58 - 22.50%. The coefficient of preference (CoP) was above unity for VBF (0, 25, 50 and 75) but less than unity for VBF- 100, showing that rams preferred silage with whole plant maize to sole VBF. This result suggests that quality of Whole plant maize silage improved when velvet bean foliage was added; however, acceptability by WAD rams was compromised.